Pattern of mobile use among medical students and its impact on health in GMC Jalaun - Verma, Santosh Kumar; Singh, Namrata (International Journal Of Community Medicine And Public Health, 2024)
Background: Mobile phone because of the ever availability and its mobility application has created a dramatic interest for youth in comparison with other communication technologies. Unfortunately, communication technology has some negative effects also. Constant usage and addiction to cell phones has affected the people physically, psychologically, and socially. Aims and objective were to assess the pattern and impact on health of mobile phone use among students of Government Medical College, Jalaun. Methods: A descriptive cross-sectional study was conducted on GMC Jalaun from October to December (3 months). All students of MBBS final year part 1 were selected as sample, so total 98 students were selected in the study. Students were requested to complete a pre-tested self-administered questionnaire. The data were analyzed by using appropriate statistical test. Results: Our study shows that mobile phone use was very high among the medical students and 54.1% of them spending 4-6 hours per day. Most of the students were frequently using mobile phone for taking pictures, videos, playing games, listening to music and internet surfing other than for calling and messaging purpose. Majority of the students used mobile phones at night (62.2%). Majority were suffered from sleep disturbance (52.1%) followed by lack of concentration (47.9%) and behavioural disorder (36.8). Out of total students, 31.6% were having refracting error. Conclusions: Our study showed pattern of mobile phone use among the medical students and it was found that mobile phone use was very high among the medical students.